Executive Functioning in Adolescents with Chronic Musculoskeletal Pain - Kristen E. Jastrowski Mano; Emily A. Beckmann; Lauren M. Fussner; Susmita Kashikar-Zuck (Children, 2020)
Adolescents with chronic pain often suffer significant impairment in physical, emotional, and social domains. Surprisingly little is known about executive functioning (EF) in youth with chronic pain or how EF deficits may contribute to functional impairment. Study participants included 60 adolescents between the ages of 12 and 17 years (M = 14.57). Thirty participants with chronic musculoskeletal pain and 30 age- and gender-matched healthy controls were recruited from a large Midwestern children’s hospital in the United States. Participants completed the Behavior Rating Inventory of Executive Functioning (BRIEF-2) as well as multiple measures of functional impairment across key domains: school, social, emotional (anxiety, depression), and physical. Adolescents with chronic musculoskeletal pain reported significantly greater EF impairment compared to healthy age- and gender-matched peers. Clinically elevated risk levels of impairment were reported across all aspects of EF, with many adolescents in the chronic pain group scoring above the clinical risk cut off for working memory (52%), inhibition (45%), and cognitive flexibility (38%). EF was also significantly related to functional impairment across all domains. Findings suggest that EF may have an impact across several critical domains of functioning for youth with chronic pain.